The trouble with Tolstoy [videorecording (DVD)]. - Yentob, Alan (Kultur, 2012)
Alan Yentob takes an epic train ride through Leo Tolstoy's Russia, examining how Russia's great novelist became her great troublemaker. Guided by the writer's confessional diaries, Yentob travels through Tolstoy's Russia looking at the life, work and legacy of the author. It reveals a difficult, restless, ferociously brilliant man with an appetite for causing trouble both for himself, his family and for the world around him due to his fundamentalist views on God, violence and government.